3D printed hybrid-dimensional electrodes for flexible micro-supercapacitors with superior electrochemical behaviours. (8th December 2020) - Tang, Kang; Ma, Hui; Tian, Yujia; Liu, Zixian; Jin, Hongyun; Hou, Shuen; Zhou, Kun; Tian, Xiaocong
ABSTRACT: Micro-supercapacitors (MSCs) with excellent electrochemical behaviours and flexibility possess great promise for portable and wearable electronic devices. A novel type of hybrid-dimensional Fe2 O3 /graphene/Ag ink is developed and extruded into MSC electrodes through the direct ink writing-based three-dimensional (3D) printing. The optimal solid-state MSC device exhibits a maximum areal capacitance of 412.3 mF cm −2 at 2 mA cm −2, a correspondingly high energy density of 65.4 μWh cm −2 and 89% capacitance retention for over 5000 charge and discharge cycles. The superior electrochemical performance is profited by the high electron transport synergistically boosted by two-dimensional graphene nanosheets and one-dimensional Ag nanowires, and the high pseudocapacitive behaviours of Fe2 O3 nanoparticles. The 3D printed MSC exhibits reliable flexibility with remarkable retention of 90.2% of its original capacitance after 500 bending cycles. The current 3D printing fabrication demonstrates an efficient route for advanced miniaturised electrochemical energy storage.